Pengaruh Kepuasan Penggunaan E-Wallet terhadap Prilaku Pembelian Generasi Milenial di Era Digital - Intan Isra’ Nur Laily Brilian (Universitas 45 Surabaya, 2024)
This research explores the influence of user satisfaction on the purchasing behavior of the younger generation in the digital era. Using a quantitative approach and multiple linear regression analysis, we analyzed the independent variables, namely the utilization, ease and security of using e-wallets. The selection population involves use by businesses aged 18 to 35 years in Indonesia. The results of the analysis show that high user satisfaction, influenced by the perception of benefits and convenience, contributes significantly to purchasing behavior, including the frequency of using evalets in transactions. These findings provide insight for e-wallet developers and marketers to understand the factors that influence consumer behavior amidst increasingly fierce digital payment industry competition. It is hoped that this research can contribute to the literature on consumer behavior in the digital era.